(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the prevalence of hypoglycemia in patients admitted to the surgical intensive care unit (ICU) and to identify risk factors associated with hypoglycemia. Methods: A cross-sectional descriptive study was conducted on 1098 patients treated in the Intensive Care Unit 2 at Viet Duc University Hospital from April 2024 to May 2025. Among them, 33 patients experienced at least one episode of hypoglycemia confirmed by venous blood glucose testing. Associated factors were analyzed using statistical tests and multivariable regression analysis. Results: Hypoglycemia occurred in 3% of ICU patients, of whom 33.3% had severe hypoglycemia. Hypoglycemia following insulin administration was observed in 48.5% of cases. The mean ICU length of stay among patients with hypoglycemic events was 16.75 days, with a mortality rate of 63.6%. Most patients with hypoglycemia had renal failure, required mechanical ventilation, and received vasopressor support. Continuous renal replacement therapy was significantly associated with an increased risk of hypoglycemia (OR = 2.83; 95% CI: 1.41-5.71; p ≈ 0.0024). Conclusion: Hypoglycemia occurred in 3% of surgical ICU patients and was frequently associated with insulin use and critical illness. Continuous renal replacement therapy was identified as a significant risk factor for hypoglycemia.